Glasproduktion i Danmark indtil slutningen af 1600-tallet og fremtidig forskning i nordisk kontekst – en status - Kock, Jan (Hikuin, 2010)
Glassmaking in Denmark until the end of the 17th century and the future study of the topic in Scandinavian context By Jan Kock For the upper part of the Danish society the period from the end of the 15th century until the beginning of the second part of the 17th century was a time with a booming economy which even allowed few noblemen and the king to erect expensive glass houses, where table ware and panes for windows were produced. The needed technology as well as the glassmakers have to be imported, because the skill to do glass was unknown in the country. This exclusive production stopped again because of a decline in the financial situation of the country. In Jutland four to five complex of glass houses are known, a couple from Zealand and then a few from Scania, see fig. 1. Most of these glass houses only existed for a short time. The knowledge about them comes from archaeological investigations and more limited also from written sources. The used technology in the known furnaces is a bit different, but clearly give an indication that the know how is taken from Central Europe. The investigations are often rather old and not reliable to the standard of today. The investigations were published in 1970. Since that time lot of new knowledge about the glass production have come up in Europe, which gives a better background to understand and to evaluate the here used technology. In the last decade there have been new interests on different places in Scandinavia to study renaissance glass houses as well as the production itself. To unite these efforts and to get a better and broader platform to work with this topic in the future a scientific conference was arranged in Malmö January 2010. The result of this meeting is presented in this volume and it is the intention, that it will be the starting of broader cooperation in form of a networking to understand the production and use of table ware as well as window panes.